ทุนทางสังคมกับธรรมนูญการจัดการตนเอง / Social Capital and Self-Management Charter - Wanlapat Suksawas, วัลลภัช สุขสวัสดิ์ / (Journal of Community Development Research (Humanities and Social Sciences), 2017)
งานวิจัยนี้มีวัตถุประสงค์หลัก คือ การศึกษาความสัมพันธ์ระหว่างความสมัยใหม่ กระบวนการรับรู้และทุนทางสังคมกับการมีส่วนร่วมทางการเมืองของประชาชนในการจัดทำธรรมนูญการจัดการตนเองขององค์การบริหารส่วนตำบลหนองอ้อ อำเภอศรีสัชนาลัย การศึกษาครั้งนี้เป็นการวิจัยเชิงปริมาณ ข้อมูลของการวิจัยมาจากการเก็บรวบรวมข้อมูลโดยใช้แบบสอบถาม ประชากรการวิจัย ได้แก่ ประชาชนที่มีอายุ 18 ปีขึ้นไป และมีชื่ออยู่ในทะเบียนบ้านในเขตองค์การบริหารส่วนตำบลหนองอ้อ กลุ่มตัวอย่างมีจำนวน 377 คน ซึ่งมาจากสุ่มตัวอย่างแบบโดยใช้หลายขั้นตอน เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถาม และวิเคราะห์ผลการวิจัยโดยใช้โปรแกรมสถิติสำเร็จรูป ผลการศึกษา พบว่า ความสมัยใหม่และกระบวนการรับรู้ไม่มีความสัมพันธ์กับการมีส่วนร่วมทางการเมืองของประชาชน แต่ทุนทางสังคมมีความสัมพันธ์กับการมีส่วนร่วมทางการเมืองของประชาชน นอกจากนี้ยังพบว่า ความไว้วางใจต่อเจ้าหน้าที่ทางการเมืองและความไว้วางใจต่อบุคคลทั่วไปซึ่งเป็นหนึ่งในองค์ประกอบของทุนทางสังคมมีอิทธิพลสูงมากในการเสริมสร้างการมีส่วนร่วมในการจัดทำธรรมนูญจัดการตนเอง ข้อเสนอแนะที่ได้จากงานวิจัยชิ้นนี้ คือภาครัฐควรให้ความรู้แก่ประชาชนถึงนวัตกรรมหรือกลไกในการตรวจสอบการทำงานของเจ้าหน้าที่รัฐและทุกภาคส่วน ควรมีส่วนร่วมในการสร้างเครือข่ายสังคมแห่งความปลอดภัย เพื่อสร้างความไว้วางใจต่อเจ้าหน้าที่ทางการเมืองและความไว้วางใจต่อบุคคลทั่วไป ซึ่งคาดหมายได้ว่าจะส่งผลดีต่อการเสริมสร้างการมีส่วนร่วมทางการเมืองของประชาชน      The main objective of this study is to investigate the relationships among modernization, cognitive engagement and social capital and people’s political participation on making self-management charter in Nor-Or Sub-district, Si Satchanalai District, Sukhothai Province. As a quantitative study, a face-to-face survey and a questionnaire were utilized as the main tools for the investigation in this study. The selection of respondents for the survey was restricted to people of voting age (18 years old and older) who were registered in Nor-Or Sub-district. The 377 samples were selected by employing multi-stage sampling. Statistical Package for the Social Sciences was utilized for data analysis. It is discovered that modernization and cognitive engagement do not have any relationship with people’s political participation. In contrast, the findings suggest a strong evidence of a link between social capital and people’s political participation on making self-management charter. Additionally, the study revealed that, trust in incumbent and interpersonal trust, as components of social capital, played the strongest role on promoting people’s political participation on making self-management charter. The results of this study could be used to provide some practical strategies for making Thai public policy. It can be suggested that all levels of government must demonstrate an innovation or mechanism in checking performance of all incumbents. In addition, social safety networks must be created by all members of society. This will allow people to present higher level of trust in incumbent and interpersonal trust, which in turn, may encourage them to participate more in all levels of politics.
Keywords: ทุนทางสังคม ความสมัยใหม่ กระบวนการรับรู้ ธรรมนูญการจัดการตนเอง ความไว้วางใจ การมีส่วนร่วมทางการเมือง; Social Capital, Modernization, Cognitive Engagement, Self-Management Charter, Trust, Political Participation